IDENTIFIKASI KEBISINGAN DAN PENGUKURAN INDEKS SUHU BASAH DAN BOLA (ISBB) DI LINGKUNGAN KERJA PT. GLOBAL ENVIRONMENT LABORATORY (PT. GEL) - Az-zahraa, Mutiara Nur; Pasaribu, Subur P. (PROSIDING SEMINAR KIMIA, 2024)
Research has been carried out on finding disturbances and measuring the wet and ball temperature index (ISBB) in the PT work environment. Global Environmental Laboratory with 24 locations. Identification of disturbances is measured using a sound level meter based on Ministerial Decree. Environment Number 48/MENLH/11-. /1996 and ISBB measurements using a heat stress monitor based on SNI 7061-2019 concerning Work Climate Measurement and Evaluation. The method used is quantitative primary data collection (based on numerical). This primary data is based on the results of disturbance measurements and ISBB values ​​which are then processed into secondary data. The secondary data that has been obtained is then analyzed and calculated. The aim is to determine the value of disturbance intensity and ISBB in the PT work environment. Global Environment Laboratory based on Minister of Industry Regulation Number 5 of 2018 concerning the Threshold Value for Physical Factors and Chemical Factors in the Workplace is 85 dBA and the heavy workload category is 27.5%. The research results show that the disturbance intensity and ISBB values ​​are below the NAB which does not endanger workers while at PT. Global Environmental Laboratory. Keywords: Noise, ISBB, NAB